Implicaciones legales de similar la terminación del contrato de trabajo por acuerdo de las partes - Mafla Quiroz, Doménica Milena (2025)
With respect to the background, it was found that the simulation of the employment relationship has been frequently practiced by workers, who apparently terminate the individual employment contract due to the legal cause of agreement between the employee and employers. The scope of the research is explanatory, the scientific research method, used at a theoretical level of knowledge, is synthetic analytical with a review of the legislation, jurisprudence and specialized doctrine in the field of study. The analysis of qualitative results was carried out using the formal interview technique. From the results obtained, it was possible to deduce that simulation in the termination of work with the consent of the parties is an illicit practice that violates workers' rights, transgresses labor law regulations and its purpose is to avoid legal obligations and the consequences that may arise from the justified termination of the contract. In short, at the beginning or end of a work activity you must go before the Ministry of Labor Relations, Labor Inspectorate, Labor Court in the absence of the above, before a multi- competent Judge, the employer and worker must be present to avoid . this type of behavior that makes work precarious. Training both workers and employees on the legal implications of simulation is important.